Spontaneous Blinking Kinetics on Paralytic Lagophthalmos After Lid Load with Gold Weight or Autogenous Temporalis Fascia Sling. (2nd April 2016) - Wambier, Sarah P. F.; Garcia, Denny M.; Cruz, Antonio A. V.; Messias, Andre
ABSTRACT: Purpose : To assess the upper eyelid kinematics during spontaneous blinking in unilateral paralytic lagophthalmos before and after upper eyelid load with gold weight (GW) or autogenous temporalis fascia (TF) sling. Design : Comparative case series. Subjects : Patients with long-standing unresolved unilateral facial palsy who underwent surgical treatment with GW ( n  = 8) or upper lid cerclage with TF ( n  = 10). The contralateral eyelid served as the control for each patient (control group). Methods : Preoperative and postoperative measurements of spontaneous blink kinematics with magnetic search coil and clinical assessment of lid margin position, lagophthalmos and ocular surface exposure, and determine amplitude, maximum velocity and main sequence of spontaneous blinks; relative amplitude of blinks to the pupil center; ocular surface exposure scores; magnitude of lagophthalmos and mid-pupil lid distances. Results : The mean (±SE) down-phase amplitude ratio between paralyzed and contralateral eyelids (blink gain) was 10.0% preoperatively for both groups and significantly increased to 29 ± 6% for the GW group ( p  < 0.05) and 23 ± 4% for the TF group ( p  < 0.05). At 6 months the gain was significant for the GW group only (32 ± 7%, p  < 0.05). There was no effect on the maximum velocity of the blinks or the main sequence of paretic and contralateral blinks with either surgery. Both procedures lowered the lid margin increasing the number of blinks that reached the pupil center. At 6 months this effect was prominent only for the GW group. Exposure keratopathy scores and lagophthalmos decreased postoperatively especially in the GW group. Conclusions : The beneficial effect of lid load surgeries result from a combination of a small increase on the spontaneous blink amplitude and a static effect due to the reduction of the distance between the lid margin and pupil center.